HUBUNGAN PENGETAHUAN BIDAN TENTANG STUNTING DENGAN PERILAKU PENDATAAN STUNTING DI PUSKESMAS TEUPIN RAYA KABUPATEN PIDIE 2021 - Zaitun; Salamah; Nurmeliana (Nusantara Hasana Journal, 2021)
Stunting is caused by a long-term lack of nutrition during the first 1,000 days of life (HPK), which is a critical period. 1000 HPK is a period of acceleration of child growth and development (gold period) which starts from the womb for 280 days of pregnancy until toddlerhood for 720 days or around 2 years. This period is a period that determines the quality of life so it is called the golden period. This period is a sensitive period because the consequences for children at this time will be permanent and cannot be corrected. For this reason, it is necessary to fulfill adequate nutrition at this age. This type of research is analytic with a cross-sectional approach. The sample in this study were midwives with a total sampling technique that used 46 people. This research was conducted at the Teupin Raya Public Health Center, Glumpang Tiga District, Pidie Regency. Data was collected by distributing questionnaires containing 20 questions. Data analysis used the chi square test, with the result that at the significance level (α) = 0.05 it indicates that p value = 0.006 <α = 0.05, so it can be concluded that Ho is rejected and Ha is accepted. So the results of the study show that there is a significant relationship between midwives' knowledge about stunting and stunting data collection behavior